Retrospective Case Series on the Treatment of Painful Diabetic Peripheral Neuropathy With Dorsal Root Ganglion Stimulation. Issue 8 (25th March 2018) - Eldabe, Sam; Espinet, Anthony; Wahlstedt, Anders; Kang, Porhan; Liem, Liong; Patel, Nikunj K.; Vesper, Jan; Kimber, Alicia; Cusack, William; Kramer, Jeffery
Abstract : Background: The dorsal root ganglion (DRG) has been identified as an important neural structure in the development and maintenance of chronic pain. We present a retrospective case series of patients with refractory painful diabetic peripheral neuropathy (PDPN) that underwent electrical stimulation of the DRG and report on changes in their overall perceived pain and complication rates. Methods: Ten diabetic males (mean age 65.2 [SD 8.8] years) with painful symptoms of the lower limbs were enrolled and trialed with up to four quadripolar percutaneous DRG stimulation leads between L2 and L5 spinal levels. Patients received a fully implantable neurostimulation system (Abbott Laboratories, Sunnyvale, CA, USA) immediately or after a successful trial period (>50% reduction in pain). Overall perceived pain was measured by visual analogue scale (VAS) at baseline, one‐week postimplantation and one‐, three‐, six‐, and twelve‐month follow‐up ( n  = 5). Results: Ten patients were included in this retrospective study. Seven of these subjects received permanent stimulator implants after successful externalized or intraoperative trials. Two of those patients subsequently required explantation, due to failure to capture primary pain area ( n  = 1) and personal reasons ( n  = 1). For the five subjects that proceeded to clinical follow‐ups, baseline VAS was reduced by an average of 63.90% (SD 21.39; p  < 0.001) postimplantation. For four patients with available 12‐month follow‐up data, mean relative reduction in overall perceived pain averaged 64.16% (SD 35.8; p < 0.001). Conclusion: Early findings from this small retrospective case series, suggest DRG is a safe and effective neuromodulation modality to improve painful symptoms in PDPN patients. Future prospective trials are required to further investigate the use of DRG stimulation for this clinical indication.